A prolonged assistantship for final‐year students. (April 2015) - Lightman, Elewys; Kingdon, Sarah; Nelson, Michael
Summary: Background: The transition from medical student to junior doctor is challenging, therefore adequate preparation during medical school is crucial for a smooth transition. Tomorrow's Doctors expects students to undertake a student assistantship, separate from the local shadowing period prior to commencing employment. Sheffield Medical School initiated a 6–week assistantship within the Yorkshire and Humber deanery. This mixed‐methodology study explores this experience from the perspective of final‐year medical students. Methods: Final‐year medical students responded to a questionnaire about anxieties surrounding their forthcoming foundation year 1 (FY1). Students were purposefully sampled and semi‐structured interviews (SSIs) were conducted, with 20 participants exploring their experience of the assistantship. Interviews were transcribed verbatim and thematic analysis was carried out. Results: The questionnaire results highlighted that most students felt anxious about becoming a FY1 doctor, and subsequent interviews demonstrate that the assistantship mostly met with students' expectations. Major themes regarding their anxieties included the value of building professional relationships, familiarisation with the work environment, level of supervision and the value of targeted teaching. Tomorrow's Doctors expects students to undertake a student assistantship Discussion: Student assistantships clearly improve preparedness and confidence in the transition to FY1 by enabling supervised, stepwise responsibility. In the future a nationally cohesive programme should be created for shadowing and assistantships matched with students' prospective jobs.